Three-Dimensional Map of Isoprognostic Zones in Glottic Cancer Treated by Transoral Laser Microsurgery as a Unimodal Treatment Strategy - Piazza, Cesare; Filauro, Marta; Paderno, Alberto; Marchi, Filippo; Perotti, Pietro; Morello, Riccardo; Taboni, Stefano; Parrinello, Giampiero; Incandela, Fabiola; Iandelli, Andrea; Missale, Francesco; Peretti, Giorgio (Frontiers in Oncology, 2018)
Introduction The Union for International Cancer Control–American Joint Committee on Cancer TNM staging system for glottic squamous cell carcinoma (SCC) includes different types of lesions defined by the involvement of specific subsites in each T category. Our study aims to identify different subcategories according to tumor local extension and determine oncologic outcomes after treatment by transoral laser microsurgery (TLM) alone. Methods We retrospectively evaluated 410 patients affected by previously untreated pT1-pT3 glottic SCC treated by TLM alone from January 2005 to December 2015 at the Departments of Otorhinolaryngology—Head and Neck Surgery, Universities of Genoa and Brescia, Italy. All patients had at least 2 years of follow-up. Clinical, radiological, surgical, and histopathological data were reviewed and tumors divided into six subcategories: I, pT1a not involving the anterior commissure (AC); II, pT1b involving the AC; III, pT2 extending superficially to the supraglottis or the subglottis; IV, pT2 infiltrating the vocal muscle; V, pT3 involving the anterior paraglottic space; VI, pT2 or pT3 with vertical extension across the AC with/without involvement of the pre-epiglottic space. Recurrence-free survival (RFS), local control with laser alone (LCL), and organ preservation (OP) were defined as the primary oncologic outcomes. Results The 2, 5, and 10-year RFS for the entire series were 85.7, 80.3, and 73.8%, LCL rates 93.8, 92.1, and 89.6%, and OP rates 96.8, 95.9, and 93.5%, respectively. However, when comparing the rates of RFS, LCL, and OP for each subcategory, important differences emerged. In particular, subcategories V and VI showed a significantly increased risk of local recurrence [hazard ratio (HR) = 9.2 and 13.3, respectively]. These subcategories also had a significantly reduced probability to achieve LCL (HR: 73.6 and 93.5, respectively) and OP (HR: 6.4 and 8.1, respectively). Conclusion The present classification in subcategories allows introducing the concept of a three-dimensional map of isoprognostic zones in glottic SCC treated by TLM alone as a useful tool in its management by a multidisciplinary tumor board.